2014
DOI: 10.1007/s10067-013-2474-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with regional rheumatic pain disorders in a population of Puerto Ricans with diabetes mellitus

Abstract: The aim of the study was to determine the prevalence and factors associated with bursitis/tendonitis disorders in Puerto Ricans with diabetes mellitus (DM). A cross-sectional study was performed in 202 adult Puerto Ricans (100 DM patients and 102 non-diabetic subjects). For each participant, a complete medical history and a musculoskeletal exam were systematically performed. Socio-demographic parameters, health-related behaviors, comorbidities, and pharmacotherapy were determined for all subjects. For DM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Diabetes has been found to be more prevalent in those with post-traumatic stress disorder (PTSD) (Trief et al, 2006), which may include survivors of 9/11, war veterans, those whose parents or grandparents were war veterans, Holocaust survivors and their offspring, among many other examples. PTSD has been established as contributing to central sensitivity (discussed under Allostatic Load & Central Sensitivity below) and therefore to a series of other persistent health complaints (Yunus, 2008(Yunus, , 2015, as well as to risk of epicondylitis (Shiri et al, 2006;Font et al, 2014). This leads us to question why this would be?…”
Section: The Stress Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes has been found to be more prevalent in those with post-traumatic stress disorder (PTSD) (Trief et al, 2006), which may include survivors of 9/11, war veterans, those whose parents or grandparents were war veterans, Holocaust survivors and their offspring, among many other examples. PTSD has been established as contributing to central sensitivity (discussed under Allostatic Load & Central Sensitivity below) and therefore to a series of other persistent health complaints (Yunus, 2008(Yunus, , 2015, as well as to risk of epicondylitis (Shiri et al, 2006;Font et al, 2014). This leads us to question why this would be?…”
Section: The Stress Connectionmentioning
confidence: 99%
“…The innervation of the Achilles (or triceps surae) is not close to the heart's innervation, so this would seem to reduce likelihood of central sensitivity from cardiac stress playing a role in Achilles tendinopathies. Font et al (2014) point to lateral epicondylitis being driven by the diabetes and peripheral vascular disease, so this may well be a feature in other connective tissue compromise. Nevertheless, it does pose the question: if central sensitivity or metabolic changes are involved in connective tissue and other musculoskeletal pain conditions, which comes first?…”
Section: Central Sensitivity and Allostatic Loadmentioning
confidence: 99%
“…The magnitude of the association is as high as 6-fold with a strong trend across the CVD risk scores ( p = 0.0005). This evidence adds to a growing body of evidence that common, soft-tissue musculoskeletal disorders, including shoulder disorders, Achilles tendinopathy, and carpal tunnel syndrome [ 30 , 63 , 68 , 69 ], may have pathophysiological bases in CVD risks. A discrete mechanism of action of CVD risk is clearer in the shoulder and Achilles where tenuous blood supply to the tendons is well defined [ 70 – 74 ].…”
Section: Discussionmentioning
confidence: 79%
“…Individual cardiovascular disease risk factors have been previously reported as risks for LE. A prior case-control study found peripheral vascular disease and diabetes mellitus were both associated with LE [ 68 ]. Diabetes mellitus has been reported to be a LE risk [ 12 ], as well as chronic hyperglycemia [ 79 ].…”
Section: Discussionmentioning
confidence: 99%